2021
DOI: 10.31348/2021/22
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pharmacological Pupil Dilation on Intraocular Lens Power Calculation in Patients Indicated for Cataract Surgery

Abstract: Purpose: To evaluate the influence of pupil dilation on ocular parameters measured by optical biometry and the influence of pupil dilation on intraocular lens (PC IOL) power calculation by using the third-generation (SRK/T) and the fourth-generation (Haigis) formula. Methods: 40 eyes of patients indicated for cataract surgery were included in this study. Each patient was examined by optical biometer firstly without artificial mydriasis (AM) and then after AM, which was achieved using local application of shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
2
0
0
Order By: Relevance
“…In addition, our study found deeper ACD and longer WTW distance (in both eyes), longer AL (right eye), and thinner LT (left eye) after pupillary dilatation. Similar findings were reported in previous studies [3537]. We also found a flatter K (left eye) prior to dilatation.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, our study found deeper ACD and longer WTW distance (in both eyes), longer AL (right eye), and thinner LT (left eye) after pupillary dilatation. Similar findings were reported in previous studies [3537]. We also found a flatter K (left eye) prior to dilatation.…”
Section: Discussionsupporting
confidence: 92%
“…From Lenstarʼs biometric measurements (AL, ACD, K1, K2, and WTW), we found that only ACD increased significantly after cycloplegia. This finding is similar to the results of studies conducted by Arriola-Villalobos et al [26] and Autrata et al [27] with the same device in the adult population. Similarly, Khambhiphant et al showed that ACD increased after pupil dilation in their study with IOL-Master in adults [28].…”
Section: Discussionsupporting
confidence: 92%